DOZ047.19: Outcomes in the management of long-gap esophageal atresia: is the Foker technique superior?. (24th June 2019) - Wiseman, A; Krishnan, J; Wanaguru, D; Langusch, C; Varjavandi, V; Jiwane, A; Dilley, A; Adams, S; Henry, G; Currie, B; Krishnan, U
Abstract: Background: Long-gap esophageal atresia (LGEA) has traditionally been managed by delayed anastamosis. However, over the last 10 years the Foker technique of esophageal growth elongation has been used. There is limited data evaluating outcomes using both techniques. Aims: The aim of this study was to compare the outcomes in LGEA repair using the traditional delayed repair technique versus the Foker technique. Methods: A retrospective chart review was done of LGEA patients at Sydney Children's Hospital between 1997 and 2016, comparing the Foker technique with the delayed repair technique. Results: There were 9 children repaired using the Foker technique, and 10 by delayed repair. There were 7 patients with Type A, 1 with Type B, and 1 with Type C in the Foker group and in the delayed repair cohort, 5 were Type A, 2 Type B, 2 Type C, and 1 Type D esophageal atresia/tracheoesophageal fistula. There were 4 males in the Foker group and 5 in the non-Foker group. Median time to join was 59 days (15–117 days) for Foker repair and 173 days (16–433 days) for delayed repair. There was no significant difference in the incidence of post-operative leak, incidence of strictures needing dilation, presence of reflux symptoms, presence of reflux esophagitis on endoscopy, proton pump inhibitor use, need for fundoplication, incidence of cyanotic spells, occurrence of recurrent fistula, and symptoms of dysphagia when comparing both groups. Data on time to oral feeds and incidence of malnutrition was incomplete. Details are shown in Table 1. Conclusions: Although the time to anastamosis was shorter in the Foker group and the incidence of post-operative leak, strictures needing dilation, need for fundoplication, and dysphagia were lower in the Foker group, the difference was not significant probably secondary to the small sample size. These results require validation in larger cohorts. Table 1 Comparison of Foker group with delayed repair group Demographic and outcome variables Foker procedure (FP) Delayed repair (DR) P value Type of OA/TOF 7 Type A 5 Type A NS 1 Type B 2 Type B 1 Type C 2 Type C 1 Type D Associated comorbidity 8 (80%) 8 (80%) NS Median age at joining 59 days (15–117) 173d (16–433) Post-operative leak 3 (33%) 8 (80%) 0.06 Number on oral feeds at discharge 7 (78%) Data Incomplete Full oral feeds at F/U 8 (89%) Data Incomplete Gastrostomy in use at F/U 1 (11%) 0 NS Strictures needing dilation/patient 6 (2–15) 9 (90%) NS Reflux symptoms at F/U 8 (89%) 8 (80%) NS PPI use at F/U 7 (78%) 8 (80%) NS Reflux esophagitis 1/5 (20%) 1/4 (25%) NS Eosinophilic esophagitis 3/5 (60%) Unknown Fundoplication 2 (22%) 5 (50%) NS Cyanotic spells 2 (22%) 0 NS Recurrent fistula 0 0 NS Dysphagia at F/U 4 (44%) 9 (90%) 0.05 Height ' z ' score at F/U −1.245 (−2.46–0.88) Data incomplete Weight ' z ' score at F/U −1.5 (−1.77 −0.34) Data incomplete